2002
DOI: 10.1212/wnl.58.7.1081
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized trial of oxandrolone in inclusion body myositis

Abstract: Oxandrolone had a borderline significant effect in improving whole-body strength and a significant effect in improving upper-extremity strength as measured by MVICT. Given these findings, further study of this drug, possibly in combination with an immunomodulating agent, is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 22 publications
1
49
0
4
Order By: Relevance
“…Timed Up and Go, which is the time it takes a patient to stand up from a chair without armrests, walk 3 m, turn around, return to the chair, and sit down, was measured as previously described. 13 The quicker of 2 trials (in seconds) was recorded. In addition, 6MWD was also measured as previously described.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Timed Up and Go, which is the time it takes a patient to stand up from a chair without armrests, walk 3 m, turn around, return to the chair, and sit down, was measured as previously described. 13 The quicker of 2 trials (in seconds) was recorded. In addition, 6MWD was also measured as previously described.…”
mentioning
confidence: 99%
“…In addition, 6MWD was also measured as previously described. 13 Statistical analysis. All outcomes were analyzed by analysis of covariance with the pretreatment baseline as a covariate and treatment as a fixed effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the use of T to enhance strength and muscle mass has been considered not only in hypogonadal [28] and aging men [29] but also in glucocorticoid induced myopathy [30,31] and in HIV and cancer-related skeletal muscle loss and wasting [32,33]. Lastly, the effect of oxandrolone, a synthetic dehydroepiandrosterone derivative, has been investigated in dystrophynopathies and inclusion body myositis [34,35]. More recently, the use of T supplementation was proposed in a clinical study in which a high incidence of hypogonadism was observed in men with various types of myopathies, such as facioscapulohumeral dystrophy, inclusion body myositis, dystrophynopathy, and metabolic myopathy, as well as DM1 [36].…”
Section: Discussionmentioning
confidence: 99%
“…38 Alemtuzumab (Campath-1), a monoclonal antibody, is directed against CD52, a cell surface molecule present on various immune cells (particularly T cells, B cells, and dendritic cells) and inducing selective immune depletion after intravenous application. Alemtuzumab was used in a controlled study in patients with sIBM.…”
Section: Therapy Of Sporadic Ibmmentioning
confidence: 99%